The Oxford Handbook of Music Education, Volume 1 2012
DOI: 10.1093/oxfordhb/9780199730810.013.0020_update_001
|View full text |Cite
|
Sign up to set email alerts
|

Children's Ways of Learning Inside and Outside the Classroom

Abstract: This article focuses on children's musical play, including that involving interactions with popular music and popular culture. It outlines features of musical play, especially as found in communities of practice in the playground, and the disjunction that may often occur between children's challenging, social, and participatory enactment of play and the pedagogical characteristics of classroom music. The article suggests a child-centered approach to music learning and teaching that endeavors to bridge the gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Two particular aspects of learning were observed in this study: implicit learning, with children participating as a group in a common activity, and explicit learning, with peers teaching each other. This reflects similar research findings on learning in informal contexts (Green, 2008;Harwood & Marsh, 2012). In line with findings from relevant studies (see Introduction), data from this study showed that learning took place in a holistic way in the performance context.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Two particular aspects of learning were observed in this study: implicit learning, with children participating as a group in a common activity, and explicit learning, with peers teaching each other. This reflects similar research findings on learning in informal contexts (Green, 2008;Harwood & Marsh, 2012). In line with findings from relevant studies (see Introduction), data from this study showed that learning took place in a holistic way in the performance context.…”
Section: Discussionsupporting
confidence: 91%
“…The key findings are grounded in the data collected from observation, interviews, and video recordings, but they are also informed by themes that have been reported elsewhere in the relevant literature (cf. Bishop & Burn, 2013;Gaunt, 2012;Grugeon, 2001;Harrop-Allin, 2010;Harwood & Marsh, 2012;K. Marsh, 2008).…”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Culturally responsive practice neither precludes nor privileges any particular teaching and learning approaches, but calls for adaptive expertise characterised by flexibility and sensitivity to context (Berryman et al, 2018). Context and teaching approaches are largely determined by the goals of music programmes, which may emphasise either presentational or participatory goals (Harwood & Marsh, 2012;Lawton, 2020). Reimer (2007) is critical of a system of music education that concentrates on large ensemble performances.…”
Section: Goals and Characteristics Of Music Programmesmentioning
confidence: 99%
“…His solution is to assert that the popular music of any culture has the most potential for engaging students with moral and ethical issues. Harwood and Marsh (2012) also explore the difference between a music education whose goal is to prepare repertoire for an audience and one which features the equal and valued participation of all. Drawing on Turino (2008), they acknowledge that neither approach is better or more natural than the other, suggesting that effective classroom learning is found in a common ground, since children develop musically in unique ways across both participation and performance.…”
Section: Goals and Characteristics Of Music Programmesmentioning
confidence: 99%